Taiwan's Democracy under threat [videorecording]
Taiwan, also known as Formosa, is home to an abundance of animal and plant life and a diverse ethnic and cultural heritage. This verdant and beautiful island, crossed by the tropic of cancer, is the principle gateway to Asian markets for North American and European business. But over the past 10 years, the Taiwanese have lived under a constant shadow; the threat of 784 Chinese missiles aimed directly at Taiwan.